2019
DOI: 10.15406/ppij.2019.07.00228
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, a natural isolate from Curcuma longa (turmeric) with high β-hematin inhibitory potential

Abstract: Natural curcuminod isolates from turmeric Curcuma longa that belongs to ginger family Zingiberaceae were collected using reversed phase preparative HPLC coupled to photodiode array detector and their in-vitro effect on β-hematin inhibition were explored. Turmeric ethanolic crude extract was tenfold less active in comparison to chloroquine positive control. Moreover, semi-quantitative and quantitative analysis results revealed that curcumin analytical standard, and to a lesser extent, the turmeric three natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Also, curcumin promotes the immune response through induction of ROS production, resulting in the activation of PPARɣ/Nrf2 and upregulation of CD36 expression in monocytes/macrophages that recital the parasiticidal activity on the blood-stage parasite when administered in mice [ 30 , 72 ]. ROS production can also be caused by the accumulation of large amounts of free heme, known as ferriprotoporphyirin [ 13 ], inducing oxidative stress which leads to parasite death. In this case, the parasite requires a free heme detoxification process by changing it to a nontoxic, inert, insoluble, crystal pigment, and blackish-brown form called hemozoin or β -hematin [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, curcumin promotes the immune response through induction of ROS production, resulting in the activation of PPARɣ/Nrf2 and upregulation of CD36 expression in monocytes/macrophages that recital the parasiticidal activity on the blood-stage parasite when administered in mice [ 30 , 72 ]. ROS production can also be caused by the accumulation of large amounts of free heme, known as ferriprotoporphyirin [ 13 ], inducing oxidative stress which leads to parasite death. In this case, the parasite requires a free heme detoxification process by changing it to a nontoxic, inert, insoluble, crystal pigment, and blackish-brown form called hemozoin or β -hematin [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result suggests that the combination of these compounds is synergistic and results in optimal efficacy. Furthermore, in vitro , curcumin 0.4 mM exhibits an inhibitory effect on the formation of β -hematin, with an efficiency of 78.8% compared to amodiaquine (91.8%) and DMSO (10.7%) [ 13 ]. Similar findings were also obtained by Akhtar et al [ 29 ], who reported that curcumin bound to chitosan nanoparticles cured rats of P. yoelii infection and inhibited the synthesis of β -hematin in vitro at IC50 (122 μ M ± 2.7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an efficient method but gain less popularity due to its cost effective purification process. Similar to the HPLC method as separation is completely based on interaction of components with absorbent material with high recovery rate, C‐18 type columns are often used for separation of curcuminoids, and in this method, 92%–99% of purity of curcuminoids can be achieved using a flow rate of 20 ml/min (Abu‐Lafi et al., 2019; Feng et al., 2017).…”
Section: Extraction Methods Of Curcuminoidsmentioning
confidence: 99%
“…Although it is more difficult for operators to use and somewhat more expensive than Conventional liquid chromatography, this method’s benefits include high-efficiency separation, continuous detection, self-governing, greater yield, and strong repeatability. , Recycling prep HPLC (up to five cycles) was utilized to achieve pure curcumin at high sample loading concentrations, and greater purity (>99.0%) of curcumin was obtained when the sample concentration was up to 6 mg. Numerous studies indicated that the semiprep HPLC approach is both practical and efficient since high-purity curcumin could be achieved. …”
Section: Purificationmentioning
confidence: 99%